A Review Paper on the Management of Food Allergies and Asthma in Schools (International Journal of Food and Nutritional Sciences, 2022)
Most of the schools will need to have strategies in place to handle children with food allergies and asthma as the incidence of these allergic diseases rises. Food allergy responses occur in schools in around 16 percent to 18 percent of the time, and include first-time reactions to food allergens. Children who have both a food allergy and asthma have a higher morbidity rate. Hospitalizations, asthma medication usage, and deadly anaphylaxis are all higher risks for these kids. Avoiding allergens lowers the risk of allergic reactions and asthma flare-ups. Oral allergen exposures are more likely to cause severe food allergy responses, while cutaneous and inhalation allergen exposures are less likely to cause severe allergic reactions. Action plans for food allergies, anaphylaxis, and asthma are tools that may be used in schools to assist guide the treatment of reactions and symptoms. The most important aspect of food allergy management is for the student to receive an accurate diagnosis and then work with their health-care provider to develop an anaphylaxis action plan.